2022
DOI: 10.1021/acs.orglett.2c00824
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reaction of Isocyanide, Ditelluride, and Mn(III) Carboxylate: Synthesis of N-Acyl Tellurocarbamate

Abstract: A multicomponent reaction of isocyanides, ditellurides and manganese(III) carboxylates under mild reaction conditions leads to the synthesis of various N-acyl tellurocarbamates. This method demonstrates good functional tolerance and broad substrate scope and, as a result, is especially suitable for the postfunctionalization of complicated molecules such as drugs. The given method can be further extended to the synthesis of selenocarbamates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…4 Addressing this limitation, Xu and Tan introduced a multicomponent reaction (MCR) involving isocyanides, ditellurides/diselenides, and manganese( iii ), leading to the synthesis of various N -acyl telluro/selenocarbamates (Scheme 1a). 5 The drawback of this methodology lies in the unsuccessful use of disulfide in the MCR, along with the requirement for excess stoichiometric equivalents of Mn( iii ) aliphatic and aromatic carboxylates as coupling partners. Hence, there remains a pressing need for a simple, direct, and environmentally friendly approach for the formation of C–S bonds to access N -acyl– N -alkyl S -thiocarbamates.…”
mentioning
confidence: 99%
“…4 Addressing this limitation, Xu and Tan introduced a multicomponent reaction (MCR) involving isocyanides, ditellurides/diselenides, and manganese( iii ), leading to the synthesis of various N -acyl telluro/selenocarbamates (Scheme 1a). 5 The drawback of this methodology lies in the unsuccessful use of disulfide in the MCR, along with the requirement for excess stoichiometric equivalents of Mn( iii ) aliphatic and aromatic carboxylates as coupling partners. Hence, there remains a pressing need for a simple, direct, and environmentally friendly approach for the formation of C–S bonds to access N -acyl– N -alkyl S -thiocarbamates.…”
mentioning
confidence: 99%
“…Therefore, exploring new selective multiple isocyanide insertion remains to be a challenging and formidable task. During our continual studies based on the isocyanide chemistry, we recently reported a silver-assisted oxidative coupling of ethers and tert -butyl isocyanide to afford β-carbonyl α-iminonitriles involving double-isocyanide insertions (Scheme d), in which a benzoxy cation was proposed as the key intermediate. These results prompted us to produce β-carbonyl α-iminonitriles by replacing ether with readily available aldehyde through direct acyl C–H bond isocyanide insertion of aldehyde.…”
mentioning
confidence: 99%